Crime, justice and criminology in the Republic of Ireland - Hamilton, Claire (European journal of criminology, 2023)
This country survey examines the core Irish criminal justice institutions; basic trends in crime and punishment over the last 50 years; and critical junctures in the debate over law and order in recent decades. Using an earlier country survey by O?Donnell (2005a) as a baseline, it charts the significant growth of the discipline of criminology within Ireland. The article argues that Irish criminal justice retains a distinctively local flavour and highlights the promise of Irish criminology in many key areas of contemporary interest.